Pengaruh Profitabilitas dan Likuiditas Terhadap Nilai Perusahaan Dengan Good Corporate Governance Sebagai Variabel Moderasi Pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Adnan, Salsabila; Aisyah Hidayati, Siti (Postgraduate, University of Mataram, 2025)
This research aims to analyze the effect of profitability, and liquidity on company value with GCG (Good Corporate Governance) as a moderating variable. This research is a associative research with a quantitative approach. In this research, sample selection was carried out using a purposive sampling method which focused on food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2019-2023 research period. By considering the established criteria, the sample was obtained from 15 companies from 92 companies so that the research data analyzed amounted to 75 observations. In this research, the panel data regression model is applied using the Random Effect Model (FEM) approach, while testing the moderating variables is carried out using Moderated Regression Analysis (MRA). The model data analysis utilizes the Eviews version 13 program. The research results show that profitability has significant effect on the company's value. Liquidity does not have a positive and insignificant effect on the company's value, GCG is able to moderate the influence of profitability on the company's value. GCG is unable to moderate the influence of liquidity on the company's value.